KERJA SAMA SISTER PROVINCE JAWA BARAT DAN AUSTRALIA SELATAN DALAM MENINGKATKAN PENDIDIKAN DI JAWA BARAT - Dina, Dina; Undang, Gunawan; Zahra, Yasmin Nur (Global Mind, 2025)
West Java is a province in Indonesia that has sister province relations with several provinces, including the Educational Cooperation with South Australia. However, there are still several obstacles, including the unpreparedness of the Regional Revenue and Expenditure Budget (APBD). The purpose of this research is to find out how the sister provinces of West Java and South Australia cooperate in improving education in West Java. This study uses qualitative methods. Data was collected through observation, interviews and documentation. Data validation was carried out through triangulation techniques. The results of the study show that the sister province cooperation has been running, but it has not been optimal due to factors that hinder the cooperation process of the sister provinces of West Java and South Australia.